Drug Data Management Application at Telu Tegal Pharmacy Using Website-Based K-Means Algorithm - Rafidatus Salsabilah Qosimah; Ginanjar Wiro Sasmito; Dyah Apriliani (GWS Tech Solution, 2025)
The rapid development of information technology provides great opportunities in increasing the efficiency and accuracy of data management, including in the pharmaceutical sector. Apotek Telu as one of the health service providers requires a system that is able to manage drug sales data effectively and provide useful insights in decision making. This study aims to build a website-based application that not only handles drug data management and sales transactions, but is also equipped with a disease trend analysis feature using the K-Means Clustering algorithm. This method is used to group drug purchase data based on patient purchase patterns, so that it can identify disease trends that often occur in a certain period. This application is built using the Laravel framework for the backend and Blade as the frontend templating system. The test results show that the application is able to manage data efficiently and display the results of disease trend analysis in the form of informative graphic visualizations, so that it can help pharmacies in planning stock and providing more targeted services.